Study on loss characteristic of polymer material for optical waveguide application - Mokhtar, Anis Shahida Niza (2005)
Communication technologies today are increasingly reliant on the manipulation of optical signals where previously electronic circuit manipulated those signals. With photonic technology, devices are no longer limited only to the silicon wafer because it also not requires broader functionality than can be offered on this traditional platform. Optical waveguides using polymer materials are attractive for telecommunication applications due to their low costs and simple processing steps compared to silica-based materials. Many advantages in term of optical properties have been proved by the polymer waveguides. Polymer waveguides are potentially useful for short distance optical interconnections. The most important characteristic of a waveguide is the attenuation or loss experienced by light wave as it travels through the waveguide. This dissertation focused on loss measurement of BCB polymer waveguides. Sample of waveguides with variation thickness have been fabricated by deposition of the polymer solution onto glass substrate. The measurement is done by using two types of wavelength that is 630nm and 1550nm. After analyzed all the coupling method, prism coupler method is considered as one of the best ways to couple large amount of light in planar optical waveguides. Furthermore it can be used to determine the loss of polymer waveguide and its characteristics. Investigation of the polymer waveguides with respect to temperature and water also done to see its stability